Work Fatigue and Response Time to Emergencies on the Morning and Night Shift Workers - Lady, Lovely Lady (JURNAL TEKNIK INDUSTRI, 2025)
Introduction: Operating 24 hours a day is unavoidable for some industries, so the industry divides working time into 3 shifts. The night shift is when the human body must rest in line with the body's circadian rhythm. Working night shifts challenges workers because they must fight their drowsiness. This has serious consequences for safety and health. Methods: This study has two groups of subjects; the first group is security workers in the industry, and the second group is nurses. Both groups of workers work in the morning and night shifts. These two groups of workers have the same job characteristics: they work whenever needed, and part of the time is used to rest or wait for conditions that must be served. This research is a naturalistic study. The respondents were 20 men who worked in the industry and 20 women who worked as nurses. Observations and data collection for morning shift work and night shift work. The observations also compared two different occupational groups. Results: The speed of response to emergency conditions was assessed by the subjects' reaction time. Reaction time is the interval of time that a person needs to respond to a stimulus. Work fatigue is assessed subjectively using an exhaustion questionnaire. The subject's reaction speed and fatigue were compared between the morning and night shift work. The two groups of workers were also compared. Low reaction speed and high work fatigue can potentially cause work errors and work accidents, so solutions are provided to overcome them.